2007
DOI: 10.1007/s10339-007-0182-y
|View full text |Cite
|
Sign up to set email alerts
|

Domain-dependent activation during spatial and nonspatial auditory working memory

Abstract: Visual system has been proposed to be divided into two, the ventral and dorsal, processing streams. The ventral pathway is thought to be involved in object identification whereas the dorsal pathway processes information regarding the spatial locations of objects and the spatial relationships among objects. Several studies on working memory (WM) processing have further suggested that there is a dissociable domain-dependent functional organization within the prefrontal cortex for processing of spatial and nonspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Consistent with a number of studies mentioned above, we assume that within the prefrontal cortex, there exists a relative specialization for auditory object working memory with the ventrolateral prefrontal cortex being involved in auditory working memory tasks (for a review see also Rämä, 2008). Thus, this region might be recruited for maintaining and rehearsing auditory material over short periods of time.…”
Section: Introductionsupporting
confidence: 69%
“…Consistent with a number of studies mentioned above, we assume that within the prefrontal cortex, there exists a relative specialization for auditory object working memory with the ventrolateral prefrontal cortex being involved in auditory working memory tasks (for a review see also Rämä, 2008). Thus, this region might be recruited for maintaining and rehearsing auditory material over short periods of time.…”
Section: Introductionsupporting
confidence: 69%
“…Many concepts have stressed a distinction between the ventral and dorsal aspects of the human LPFC in working memory, though different hypotheses on the nature of their functional segregation exist (Curtis & D’Esposito 2004). One view relates this specialization to the processing of spatial and non-spatial, i.e., object related, information (Romanski 2004, Rämä 2008). Other authors, however, have argued, that dorsal and ventral prefrontal cortices perform qualitatively different operations such as individual item processing vs. the organization of multiple pieces of information (Müller & Knight 2006; Blumenfeld & Ranganath 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A comparable result was observed by Saults and Cowan (2007) who attributed the equal performances to central capacity (for the moment we ignore the modality-specific effects). Similarly, in an fMRI study, Arnott et al (2005) observed activations in the parietal cortex if locations of sounds had to be memorized similar to those found for visual objects but anterior temporal activations if the sound pattern was relevant (Altmann et al, 2007; see also Rä mä , 2008).…”
Section: Spatial Information Reconsideredmentioning
confidence: 89%